Analisis Pengaruh Kompetensi Sosial, Efikasi Diri dan Berbagi Pengetahuan Terhadap Kinerja Pegawai Pada Sekolah Tinggi Ilmu Ekonomi Semarang - Yovita Mumpuni Hartarini; Sopi; Zumrotun Nafiah (CV. Ulil Albab Corp, 2022)
This study aims to analyze the influence of social competence, self-efficacy and knowledge sharing on ​​employee performance at a private higher education institution in the city of Semarang, namely Semarang Schools of Economics. In this study, the sampling was carried out using purposive sampling and during the distribution process, a sample of 66 respondents was obtained. The analysis technique of this research uses multiple regression analysis. This research also conducted instrument test of reliability and validity, classical assumption test, hypothesis testing through t test, model feasibility test through F test and coefficient of determination. The results showed that social competence had a positive effect on employee performance. The direction of the positive regression coefficient indicates a positive influence of social competence on employee performance. Self efficacy has a positive effect on employee performance. The direction of the positive regression coefficient indicates a positive influence of self-efficacy on employee performance, Knowledge sharing has a positive effect on employee performance. The direction of the positive regression coefficient indicates a positive influence of knowledge sharing on employee performance.